Peningkatkan Hasil Belajar Pendidikan Agama Islam Siswa pada Materi Beriman Kepada Kitab – Kitab Allah Melalui Metode Diskusi - Eny Lutfi; Saipul Bahroni; Elfa Frinadra (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2022)
This study aims to determine the effect of implementing discussion strategies on student learning outcomes in the material Belief in the Books of Allah in Islamic Religious Education (PAI) learning in the classroom. This study uses the Classroom Action Research (CAR) method which is carried out in two cycles, with each cycle consisting of planning, implementation, observation, and reflection stages. The subjects of the study were 30 students who took part in PAI learning. The results of the study showed that implementing discussion strategies can significantly improve student learning outcomes. In the first cycle, 63.3% of students achieved scores above the KKM (75), while in the second cycle, the percentage of students who completed increased to 83.3%. The implementation of discussion strategies also increased students' active involvement in learning and strengthened critical thinking skills and group cooperation. These findings indicate that discussion strategies are an effective alternative to improve student learning outcomes and understanding in PAI learning, especially in complex materials that require deep reflection, such as Belief in the Books of Allah.